Trinidad and Tobago : Staff Report for the 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2013)
This 2013 Article IV Consultation highlights that the economy of Trinidad and Tobago is poised for a modest recovery in 2013, after disappointing growth in 2012 that was owing to largely supply constraints, including maintenance operations in the energy sector and an industrial dispute in the nonenergy sector. The IMF staff projects real GDP growth of some 1.5 percent in 2013, with risks slightly to the downside, should development spending be under-executed. Headline inflation rose to 9.3 percent in 2012. Executive Directors welcomed the signs of economic recovery, fueled by growth of the nonenergy sector.